Physiological and metabolic demands of running and cycling in well-trained triathletes - Jacobs, M. W.; Feuerbacher, J. F.; Bloch, W.; Schumann, M. (International Journal of Sports Medicine, 2026)
Overall performance in triathlon is largely determined by cycling and running performances, which depend on maximal and submaximal physiological factors. This study assessed the associations of these physiological factors between running and cycling in well-trained triathletes. Thirty-one male triathletes (age: 25±1 y; maximal aerobic capacity: 63.6±0.7 mL min-1 kg-1), competing in Olympic to long distance triathlon, participated in this study. Physiological parameters (maximal aerobic capacity, movement economy, fractional utilization at 4 mmol L-1 blood lactate, energy consumption, and maximal fat oxidation rate) were assessed using a combined step and a ramp protocol for cycling and running, respectively. Testing sessions were separated by 48-96 hours. Movement economy and energy consumption were analyzed at 50, 60, and 70% of each participant`s maximal aerobic capacity. All cycling performance parameters correlated with those of running. Thereby, the maximal aerobic capacity showed a correlation of p=0.81, and the relative use of maximal aerobic capacity at a 4 mmol L-1 lactate concentration a correlation of p=0.49. Furthermore, the maximal fat oxidation rate was statistically correlated with p=0.44, while movement economy (p=0.79-0.85) as well as energy consumption (p=0.46-0.52) showed statistical correlations over all three intensity zones (50-70%, all p < 0.050). In well-trained triathletes, central parameters like maximal aerobic capacity show strong correlations between cycling and running, while submaximal, peripheral indicators appear more discipline-specific. Thus, training should be aligned with the targeted physiological adaptation.